Computed tomography enterography increases the ability of endoscopy to differentiate Crohn's disease from intestinal Behçet's disease - Yang, Hong; Zhang, Huimin; Liu, Wei; Han, Wei; Guo, Tao; Lai, Yamin; Tan, Bei; Wang, Congling; Chen, Minhu; Gao, Xiang; Ran, Zhihua; Liu, Zhanju; et al. (Frontiers in Medicine, 2022)
Background: Distinguishing Crohn's disease (CD) and intestinal Behcet disease (BD) is difficult in clinical practice. Aims: To evaluate the ability of computed tomography enterography (CTE) to enhance the diagnostic value of endoscopy in differentiating CD from intestinal BD and to establish differential diagnosis models. Methods: A total of 113 CD and 70 intestinal BD from 7 tertiary inflammatory bowel disease centers were enrolled. Univariate and multivariate analysis were used by SAS 9.2 software. Three differential scoring models based on the multivariate analysis of endoscopic features alone (model 1), endoscopic features combined with clinical symptoms (model 2), and endoscopic features combined with clinical symptoms and imaging features(model 3) were established. Results: The results showed model 2 increased the efficacy of model 1 in differential diagnosis and model 3 had the highest accuracy of 84.15% at a cut-off value of 2 points. The scoring of model 3 was as follows: genital ulcer (-3 points), skin lesions (-3 points), oval ulcer (-2 points), longitudinal ulcer (1 point), number of ulcers > 5 (3 points), inflammatory polyps (2 points), mucosal severe-enhancement (2 points), and fibrofatty proliferation (1 point). Conclusions: Clinical symptoms and CTE increased the ability of endoscopy to differentiate CD from intestinal BD.